Implementasi model two stay two stray untuk meningkatkan pemahaman konsep kegiatan ekonomi di sekolah dasar - Gestiani, Adya Resti; Istiyati, Siti; Hadiyah, Hadiyah (Universitas Sebelas Maret, 2021)
The research objective is improving the student’s understanding by using the Two Stay Two Stray (TSTS) model. This research is class action research that consists of 2 cycles. The subject is 35 students of 4 th grade of Pulisen State Elementary School Boyolali. Data collection techniques are conducted through observation, interviews, documentation, and tests. Data analysis techniques used are data reduction, data display, and conclusions. To determine the result of student learning outcomes, this research used source triangulation, and techniques. This research shows that students be able to comprehend the concept of economic activity increases. The first cycle result is classical pass percentage reach 75,76%. It increases in the second cycle become 91,18%. Based on observations and data, the conclusion of the Two Stay Two Stray (TSTS) model in this research could improve the understanding of the concept of economic activity. The implication of the TSTS model is that two people live in a group and two other people visit another group.